2020
DOI: 10.1111/gwao.12508
|View full text |Cite
|
Sign up to set email alerts
|

Navigating uncertainty, employment and women’s safety during COVID‐19: Reflections of sexual assault resistance educators

Abstract: COVID‐19 affects women in ways unique to the impacts of structural inequalities related to gender, sexuality, disability, race, and socioeconomic status. In this article, we reflect on our own experiences of the pandemic, as feminist students, workers, and sexual assault resistance educators located in a Canadian post‐secondary setting. Situating ourselves within feminist responses to sexual violence prevention, as facilitators of the EAAA sexual assault resistance education program for university women, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
(47 reference statements)
0
15
0
1
Order By: Relevance
“…It will be essential to actively seek to capture the lessons that the collective responses to the COVID‐19 crisis have provoked and demanded, so that the ‘right lessons’ are learned, to medicate against a cycle of further crises becoming the order of the day (Branicki, 2020; Janse van Rensburg & Smith, 2020). Capturing and reflecting these emerging social patterns will be critical in ensuring that the much‐needed learning informs collective choices that can serve the common good.…”
Section: Discussionmentioning
confidence: 99%
“…It will be essential to actively seek to capture the lessons that the collective responses to the COVID‐19 crisis have provoked and demanded, so that the ‘right lessons’ are learned, to medicate against a cycle of further crises becoming the order of the day (Branicki, 2020; Janse van Rensburg & Smith, 2020). Capturing and reflecting these emerging social patterns will be critical in ensuring that the much‐needed learning informs collective choices that can serve the common good.…”
Section: Discussionmentioning
confidence: 99%
“…52 "This pandemic disproportionately affects marginalized communities in ways unique to the impacts of structural inequalities regarding to gender, race, disability, sexuality, and socioeconomic status." 53 Restrictive global policies for controlling COVID-19 pandemic will intensify "sexual and reproductive health and justice inequities": 54 Intimate partner violence (IPV) is also commonly referred to as DV. It includes SV, physical violence (PV), stalking, and psychological aggression by a present or former intimate partner.…”
Section: Overview Of DV Against Women and Children During Covid-19mentioning
confidence: 99%
“…The evidence showed that the chronic effects of child sexual abuse were anxiety, feelings of isolation and stigma, poor self-esteem, depression, and self-destructive behavior, a tendency toward re-victimization, substance abuse, and sexual maladjustment. 52 “This pandemic disproportionately affects marginalized communities in ways unique to the impacts of structural inequalities regarding to gender, race, disability, sexuality, and socioeconomic status.” 53 Restrictive global policies for controlling COVID-19 pandemic will intensify “sexual and reproductive health and justice inequities”: 54…”
Section: Overview Of DV Against Women and Children During Covid-19mentioning
confidence: 99%
“…The pandemic has exacerbated the occurrence of many forms of gender-based violence and the impact on victims. For example, there is growing evidence that domestic violence (e.g., IPV and child abuse) increased during the pandemic (Boxall et al, 2020; Bradbury-Jones & Isham, 2020; Gosangi et al, 2021; Leslie & Riley, 2020; Peterman & O’Donnell, 2020; Piquero et al, 2021) and that the conditions of the pandemic have facilitated the occurrence of human trafficking (particularly vulnerable youth; Todres & Diaz, 2021) and sexual assault (Janse van Rensburg & Smith, 2021). Risk factors for gender-based violence, such as unemployment/financial strain, substance use, isolation, depression, and anxiety have increased during the pandemic (American Psychological Association, 2020; Czeisler et al, 2020; Peterman & O’Donnell, 2020).…”
mentioning
confidence: 99%